THE EFFECT OF DUOLINGO ON THE WRITING COMPETENCY OF THE TENTH GRADE STUDENTS OF SMK N 1 SUKASADA IN ACADEMIC YEAR 2017/2018 - Budiani, Ivan (Jurnal Pendidikan Bahasa Inggris Indonesia, 2020)
This research aimed to investigate whether or not there was a significant effect of the use of Duolingo on the writing competency of the tenth grade students of SMK N 1 Sukasada in academic year 2017/2018. This quasi-experimental research employed post-test only control group design. The population of this research was all the tenth grade students of SMK N 1 Sukasada. This research administered cluster random sampling to determine the sample. The independent sample t-test was administered to examine the equality of both groups and decided X AP1 became the experimental group and X AP2 as the control group. The treatment was given to both groups in which the experimental group treated by using Duolingo and the control group was treated by using conventional teaching media. At the end of the treatment, the post-test was administered to both groups and the result was analyzed using descriptive and inferential statistics by applying independent sample t-test. Based on the result of the descriptive analysis, the students in experimental group could gain better score than the students in control group. Moreover, the result of inferential analysis shows that the result of the independent sample t-test which tobs was higher than tcv. The result of the questionnaire also shows that students like to use Duolingo in the classroom and it helps them in their writing. It means that the implementation of Duolingo contributes significant effect to students? writing competency of the tenth grade students of SMK N 1 Sukasada in academic year 2017/2018.